Silencing of STE20‐type kinase MST3 in mice with antisense oligonucleotide treatment ameliorates diet‐induced nonalcoholic fatty liver disease. Issue 5 (23rd April 2021) - Caputo, Mara; Kurhe, Yeshwant; Kumari, Sima; Cansby, Emmelie; Amrutkar, Manoj; Scandalis, Eli; Booten, Sheri L.; Ståhlman, Marcus; Borén, Jan; Marschall, Hanns‐Ulrich; Aghajan, Mariam; Mahlapuu, Margit
Abstract: Nonalcoholic fatty liver disease (NAFLD) is emerging as a leading cause of chronic liver disease worldwide. Despite intensive nonclinical and clinical research in this field, no specific pharmacological therapy is currently approved to treat NAFLD, which has been recognized as one of the major unmet medical needs of the 21st century. Our recent studies have identified STE20‐type kinase MST3, which localizes to intracellular lipid droplets, as a critical regulator of ectopic fat accumulation in human hepatocytes. Here, we explored whether treatment with Mst3 ‐targeting antisense oligonucleotides (ASOs) can promote hepatic lipid clearance and mitigate NAFLD progression in mice in the context of obesity. We found that administration of Mst3 ‐targeting ASOs in mice effectively ameliorated the full spectrum of high‐fat diet‐induced NAFLD including liver steatosis, inflammation, fibrosis, and hepatocellular damage. Mechanistically, Mst3 ASOs suppressed lipogenic gene expression, as well as acetyl‐CoA carboxylase (ACC) protein abundance, and substantially reduced lipotoxicity‐mediated oxidative and endoplasmic reticulum stress in the livers of obese mice. Furthermore, we found that MST3 protein levels correlated positively with the severity of NAFLD in human liver biopsies. In summary, this study provides the first in vivo evidence that antagonizing MST3 signaling is sufficient to mitigate NAFLD progression in conditions of excess dietary fuels and warrants future investigations to assess whether MST3 inhibitors may provide a new strategy for the treatment of patients with NAFLD.